Woman and Womanhood in the Posters of the Great War - Běhal, Jaroslav (Univerzita Pardubice, 2019)
The aim of this bachelor thesis is to analyze a shift in the depiction of women in various British posters during the First World War (1914-1918). The first chapter provides a theoretical background to British womanhood prior to the war (1910-1914), as well as during the course of the conflict until its end in 1918. The second chapter examines posters depicting prevailing gender stereotypes of women that appeared in the early years of the war. The third chapter deals with posters portraying women in roles that conflict with or conform to the gender perception of femininity.
Žena a ženství v plakátech z první světové války
Keywords: Britain; women; posters; womanhood; Great War; perception of femininity; Británie; ženy; plakáty; ženství; velká válka; vnímání ženskosti